The surface layers structure of differently oriented single titanium nickelide crystals subjected to ion implantation. (July 2016) - Meisner, L.L.; Poletika, T.M.; Girsova, S.L.; Meisner, S.N.
Abstract: The structure of the surface and near-surface layers of titanium nickelide (NiTi) single crystals having [111]В2 and [001]В2 orientation relative to the direction of Si-ion beam treatment was investigated. It was found that the orientation effects of selective sputtering and the channeling control the thickness of the oxide and amorphous layers, the depth of penetration of ions and impurities, the distribution of Ni with depth. Different scenarios of deformation microstructure evolution are observed in the near-surface layers of NiTi crystals having of 'soft' orientation [111]В2 and 'rigid' orientation [001]В2 . Highlights: Surface layers structure of NiTi single crystals depends on the ion implantation geometry. Selective sputtering and channeling control the thickness of surface layers. The orientation affects the microstructure of near-surface layers.